Tax-1 and Tax-2 similarities and differences: focus on post-translational modifications and NF-κB activation - Shirinian, Margret; Kfoury, Youmna; Dassouki, Zeina; El Hajj, Hiba; Bazarbachi, Ali (Frontiers in Microbiology, 2013)
ABSTRACT Although human T-cell leukemia virus type 1 and 2 (HTLV-1 and HTLV-2) share similar genetic organization, they have major differences in their pathogenesis and disease manifestation. HTLV-1 is capable of transforming T lymphocytes in infected patients and subsequently leads to adult T cell leukemia/lymphoma (ATL) whereas HTLV-2 is not clearly associated with lymphoproliferative diseases. Numerous studies have provided accumulating evidence on the involvement of the viral transactivators Tax-1 versus Tax-2 in T cell transformation. Tax-1 is a potent transcriptional activator of both viral and cellular genes. Tax-1 posttranslational modifications and specifically ubiquitylation and SUMOylation have been implicated in NF-кB activation and may contribute to its transformation capacity. Although Tax-2 has similar protein structure compared to Tax-1, the two proteins display differences both in their protein-protein interaction and activation of signal transduction pathways. Recent studies on Tax-2 have suggested ubiquitylation and SUMOylation independent mechanisms of NF-кB activation. In this present review, structural and functional differences between Tax-1 and Tax- 2 will be summarized. Specifically, we will address their subcellular localization, nuclear trafficking and their effect on cellular regulatory proteins. A special attention will be given to Tax-1/Tax-2 post-translational modification such as ubiquitylation, SUMOylation, phosphorylation, acetylation, NF-кB activation and protein-protein interactions involved in oncogenecity both in vivo and in vitro.